Bending characteristics of carbon nanotubes: Micropolar elasticity models and molecular dynamics simulations. Issue 1 (1st December 2021) - Izadi, Razie; Tuna, Meral; Trovalusci, Patrizia; Fantuzzi, Nicholas
Abstract: The present paper aims at evaluating non-classical continuum parameters for each class of armchair and zigzag single-walled CNTs focusing on the scale effect in their flexural behavior observed in molecular dynamics (MD) simulations. Through a non-linear optimization approach, the bending rigidities obtained from atomistic simulations are compared to those derived from non-classical continua. For MD simulations, a novel method ensuring pure bending is introduced and for continuum modeling, micropolar, constrained micropolar, and modified couple stress theories are employed. The results reveal that adopted non-classical theories, notably micropolar theory, provide reasonable outcomes with an obvious failure of classical Cauchy theory.